(untitled) (Fiep Bulletin - online, 2017)
The physical education, considering the current studies of the area, theoretically advanced to overcome the paradigm competitivista and technicalities, but still plays the competitiveness of formal sport. Thus, we highlight and reinforce the need for philosophical questions with the aim to find methodological alternatives to the classes of Physical Education, modeled on values other than the excessive appreciation of the performance. Therefore, this study aimed to reflect on the competition and cooperation in physical education classes at school. To achieve it, we revisit the cooperative games through literature. Then, on the literature presented here, it is possible to realize the educational potential of cooperative games, allowing the emergence of a cooperative ethics.